Pelatihan pembuatan Batik Jumputan dan sosisalisasi strategi pemasaran bagi kelompok PKK di Desa Pojok - Bambang Harjito; Dionysius Deva Andraresa Kumara; Nur Ayni Fitri; Alfina Raditia Aulia; Alifio Radia Paradis; Herliana Sari Widiyani; Pramesti Ayu Pitaloka (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2024)
Pojok Village, Tawangsari, Sukoharjo Regency is one of the villages that has yet to develop much in entrepreneurship. Because of this, the village government continues to support various activities in the field of entrepreneurship, such as MSME workshops and outreach, as well as the establishment of a village-level MSME community they recently wanted to do. Therefore, to support this activity, the UNS KKN Team in Pojok Village also assisted the government program by holding Jumputan Batik Marketing Strategy Socialization and Jumputan Batik Making Training to provide business ideas well as training to inspire Pojok Village business enthusiasm. The implementation method is to conduct educational socialization first to provide an understanding of jumputan batik and its potential from an economic perspective and then be given training in jumputan batik making. After the socialization and training were carried out, it was discovered that the participants better understood how to make and market jumputan batik. This is evidenced by the data obtained through questionnaires filled out by the participants before and after the activity. The analysis results show that the percentage of participants' knowledge has increased from below the 50% conformity point to above 50%.